TEACHING MODULE: BUSINESS IN SYNERGY WITH SOCIOLOGY LEARNING SUBJECT: EFFORTS TO EMPOWER COMMUNITY CULTURE IN THE WORLD OF EDUCATION - Aida Dwipriwanti; Wening Patmi Rahayu; Andy Prasetyo Wati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the potential synergy between business teaching modules and sociology subjects as an effort to empower community culture within the educational context. Traditionally, business education has been predominantly focused on rational economic aspects, neglecting the social and cultural dimensions inherent in society. Using a Systematic Literature Review (SLR) approach, this research reviewed 15 scholarly articles published between 2021 and 2025, applying the PRISMA framework for systematic identification and inclusion. The inclusion criteria involved studies discussing the integration of business learning with socio-cultural values within secondary and higher education contexts. The findings reveal that integrating business and sociology in educational settings plays a crucial role in nurturing social entrepreneurs grounded in cultural values and ethical awareness. Teaching modules designed through this interdisciplinary approach enhance students’ social responsibility, ethical consciousness, and sensitivity to local wisdom. Furthermore, such integration strengthens the relevance of education to real-life community contexts and supports cultural preservation as part of the learning process. Therefore, the development of interdisciplinary teaching modules between business and sociology represents a strategic step toward fostering globally competitive, socially responsible, and culturally rooted young generations.